Lipids and pigment-protein complexes of photosynthetic apparatus of Deschampsia antarctica Desv. plants under UV-B radiation - Taran, N.Yu.; Storozhenko, V.O.; Svietlova, N.B.; Topchiy, N.M. (Вiopolymers and Cell, 2012)
Aim. To investigate structural and functional modifications of major components of photosynthetic membranes of endemic antarctic species D. antarctica under UV-B radiation. Methods. For quantitative determination of photosynthetic membrane components we used Arnon’s method (for chlorophylls and carotenoids); separation of carotenoids was carried out by Merzlyak’s method; polar lipids were isolated by Zill and Harmon method in modification of Yakovenko and Mihno; glycolipids separation and identification we carried out by Yamamoto method; and sulfoquinovosyl diacylglycerol content was determined by Kean method. The separation, disintegration and determination of pigment-protein complexes of chloroplasts were carried out by Anderson method. Authenticity of differences between the mean arithmetic values of indices was set after the Student criterion. Differences were considered as reliable at p 0.05. Results. We determined structural and functional changes in lipids, carotenoids and pigment-protein complexes at the photosyntetic apparatus level in D. antarctica plants under UV-B radiation. Conclusions. Adaptation of D. antarctica plants to UV-B radiation is accompanied by a cascade of physiological and biochemical rearrangements at the level of photosynthetic apparatus, manifested as the changes in pigment, lipid and pigment-protein complexes content.